PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MASKARA O TWO O PADA PLATFROM E-COMMERCE SHOPEE - Nuriddini Sri Rizki; Sindrawati Sindrawati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the effect of price and product quality on the decision to purchase O Two O mascara on the Shopee e-commerce platform. Technological developments have changed consumer behavior in online shopping, where ease of access, promotions, and product reviews influence consumer choices. The research method used is quantitative with a positivistic approach, involving 104 respondents selected through purposive sampling. Data were collected through an online questionnaire and analyzed using multiple linear regression to test the influence of price and product quality variables on purchasing decisions. The results of the study indicate that product quality has a positive and significant effect on purchasing decisions, while price, although positive, is not significant. This indicates that consumers prioritize durability, reliability, and the results of O Two O mascara makeup over price variations in their purchasing decisions. The implications of this study emphasize the importance of manufacturers maintaining product quality and packaging design to retain consumer trust, while pricing strategies can be optimized to attract new consumers without compromising quality perception. This study provides insights for cosmetics manufacturers and e-commerce marketers to understand consumer behavior and formulate effective marketing strategies in the context of digital commerce.